A dataset of higher-order Ambisonic room impulse responses and 3D models measured in a room with varying furniture - Gotz, Georg; Schlecht, Sebastian J.; Pulkki, Ville (2021 Immersive and 3D Audio: From Architecture to Automotive, I3DA 2021, 2021)
This paper presents Motus, a new dataset of higher-order Ambisonic room impulse responses. The measurements took place in a single room while varying the amount and placement of furniture. 830 different room configurations were measured with four source-to-receiver configurations, resulting in 3320 room impulse responses in total. The dataset features various furniture object placements, including non-uniform distributions of absorptive material and cases with occluded direct paths between source and receiver. All acoustic measurements are accompanied by matching 3D models and 360°-photographs of the room. After describing the dataset, we demonstrate its usage with a reverberation time analysis. The analysis reveals that most of our measurements follow the expected relationship between absorption area and reverberation time. Some exceptional cases feature particular room acoustic phenomena, such as non-uniform absorption area distributions or multi-slope decays. Additionally, we show with a large number of measurements that furniture placement can significantly affect the reverberation time of a room. The dataset can be used to investigate room acoustic topics such as the acoustic effects of absorber placements or the decay behavior of rooms.
CRIS-Team Scopus Importer:2023-11-06
Keywords: Acoustic measurement; Dataset; Room acoustics; Room impulse response; Varying furniture; Virtual reality